IMPLEMENTASI BAURAN PROMOSI DALAM MENINGKATKAN JUMLAH JAMAAH UMRAH PT ARMINAREKA PERDANA JAKARTA PUSAT - Navira Kusumaningsih (Jurnal Manajemen Dakwah, 2020)
The purpose of this study is to find out how the Implementation of The Promotion Mix in Increasing the Number of Umrah Pilgrims of PT Arminareka Perdana and to know the supporting factors and inhibitions of promotional mix activities at PT Arminareka Perdana. The research method used is a qualitative method with a descriptive approach and uses data collection techniques through interviews, observations, and documentation.From the results of the research it can be concluded that the promotional mix used by PT Arminareka Perdana is in accordance with kotler and Armstrong's theory which states that the variables contained in the promotional mix there are five, namely advertising in the form of brochures and company profiles printed. Sales promotion through incentives, ease of installment of Umrah costs and follow travel fair activities. Public relations through publicity, lobbying, building trust and good relationships, as well as being responsible. Personal sales through a process of approaching, presenting, and overcoming objections. Direct marketing by phone, WhatsApp, television, website, e-mail, blog. Keywords : Implementation and Promotional Mix